The Cultural Diffusion of the Fertility Transition: Evidence from Internal Migration in 19th Century France - Guillaume Daudin; Raphaël Franck; Hillel Rapoport (Institute for the Study of Labor (IZA), 2016)
France experienced the demographic transition before richer and more educated countries. This paper offers a novel explanation for this puzzle that emphasizes the diffusion of culture and information through internal migration. It tests how migration affected fertility by building a decennial bilateral migration matrix between French regions for 1861-1911. The identification strategy uses exogenous variation in transportation costs resulting from the construction of railways. The results suggest the convergence towards low birth rates can be explained by the diffusion of low-fertility norms by migrants, especially by migrants to and from Paris.
Keywords: J13; N33; O15; 330; fertility; France; demographic transition; migration